2010
DOI: 10.1149/ma2010-02/9/585
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Nonaqueous Electrolyte on Lithium-Ion Insertion in Nanostructured V2O5

Abstract: not Available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Previously, the presence of TBA in solution has been shown to decrease the F − concentration by almost half. 26 The third electrolyte, containing LiClO 4 salt in place of LiPF 6 , was chosen as a non-fluorine-containing control. In preparation for the XPS and ToF SIMS analyses, discussed below, a total of four electrode samples were cycled in each electrolyte, with excellent repeatability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, the presence of TBA in solution has been shown to decrease the F − concentration by almost half. 26 The third electrolyte, containing LiClO 4 salt in place of LiPF 6 , was chosen as a non-fluorine-containing control. In preparation for the XPS and ToF SIMS analyses, discussed below, a total of four electrode samples were cycled in each electrolyte, with excellent repeatability.…”
Section: Resultsmentioning
confidence: 99%
“…25 Although this HF/oxide reaction process has not yet been directly observed in TiO 2 , it has previously been identified in the V 2 O 5 cathode system, where self-catalytic formation of HF led to a conversion reaction in the cathode during cycling. 26 One potential method to address this concern has been to add thin sacrificial layers of oxide that preferentially react with the HF and protect the active material, which Xiong and coworkers demonstrated using V 2 O 5 coatings on LiNiO 2 cathodes. 27 However, the question still remains as to how the presence of HF affects the lithiation of these oxide materials from a mechanistic standpoint.…”
Section: Introductionmentioning
confidence: 99%
“…Under the described conditions, vanadium dissolution can be expected, but only a few parts per million of vanadium were found in the electrolyte. Wu et al revealed that traces of water present in the battery electroactive core can lead to HF formation. HF is reacting with V 2 O 5 cathodes through a self-catalyzed process, both at open circuit and under potential.…”
Section: Introductionmentioning
confidence: 99%